Development of Wall Material Usage in Merauke - Yosi Valentina Simorangkir,; Anton Topan,; Muchlis Alahudin,; Henry Soleman Raubaba,; Tiyans Syahrul Ivandy, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Some forms of buildings in Indonesia, especially in the Papua region, South Papua Province, Merauke Regency slowly began to change even not a few were lost and replaced by new settlements or new industrial buildings. These changes generally begin with changes in the form and function of buildings to changes in the mass order of settlements. Changes in form are easily recognized by changes in building elements, both at the foot, body and head of the building. This condition is certainly not a problem if the changes that occur are intended to create better residential housing. The use of materials in Merauke Regency has changed along with technological developments, especially in the field of architecture. In the beginning, indigenous people used natural materials to make dwellings and until now use red brick material to glass as a building wall. This study on changes in the use of building materials uses a qualitative approach with a case study as its strategy. The data collection method is carried out by observation, survey and other secondary data collection.